PENGARUH LDR DAN BOPO TERHADAP PERUBAHAN LABA PADA PERBANKAN DENGAN NIM SEBAGAI VARIABEL MODERATING - Supriyanti, Luluk; Astohar, Astohar (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2015)
This study aims to determine whether the independent variables thatOperating Expenses to Operating Income and Loan to Deposit Ratio, andNet Interest Margin as a moderating variable jointly significantly affectearnings changes. As well as to determine which variable partial effect onearnings in the banking changes listed in Indonesian Banking Directory.Based on the above objectives, the study was conducted using purposivesampling method, meaning that the sample in this study were selected basedon specific criteria. The sample in this study from the year 2006 - 2012amounted to 90 banks. Data collection techniques based on secondary data.In this study, the secondary data obtained from the financial statements ofbanks registered in Indonesian Banking Directory in the year 2006-2012 .The results of hypothesis testing using t-test, showed that thevariable BOPO ratio has no significant influence on changes in income andLDR have a significant negative effect and not to changes in bank earnings .As for testing moderating ie, the variable is not a variable net NIMmoderating influence of variables on BOPO and LDR variables to changesin earnings in the bank listed in the directory of Indonesian banking (DPI).